2021
DOI: 10.1021/acs.jmedchem.1c00551
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Hyperstable Noncanonical Plant-Derived Epidermal Growth Factor Receptor Agonist and Analogs

Abstract: Here, we report the discovery of the first plant-derived and noncanonical epidermal growth factor receptor (EGFR) agonist, the 36-residue bleogen pB1 from Pereskia bleo of the Cactaceae family. We show that bleogen pB1 is a low-affinity EGFR agonist using a suite of chemical, biochemical, cellular, and animal experiments which include incisor eruption and wound-healing mouse models. A focused positional scanning pB1 library of Ala- and d-amino acid scans yielded a high-affinity pB1 analog, [K29k]­pB1, with a 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 78 publications
1
28
0
Order By: Relevance
“…We used a mass spectrometry (MS)-driven approach to profile hev-like peptides in the aqueous extract of oats, and selected cereals and legumes, including B. maxima , C. cajan , C. lacryma , E. canadensis , G. max , P. vulgaris , H. jubatum , H. vulgare , S. cereale , S. bicolor , T. aestivum , V. umbellate , V. radiata , V. unguiculata , and V. angularis ( Loo et al, 2016 , 2017 , 2021a , b ; Tam et al, 2018 ; Kam et al, 2019a , b ; Supplementary Figures 1 – 19 ). Since hev-peptides contain 38–42 amino acids and eight cysteine residues, we focused on peaks around 4 kDa in their MS profiles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a mass spectrometry (MS)-driven approach to profile hev-like peptides in the aqueous extract of oats, and selected cereals and legumes, including B. maxima , C. cajan , C. lacryma , E. canadensis , G. max , P. vulgaris , H. jubatum , H. vulgare , S. cereale , S. bicolor , T. aestivum , V. umbellate , V. radiata , V. unguiculata , and V. angularis ( Loo et al, 2016 , 2017 , 2021a , b ; Tam et al, 2018 ; Kam et al, 2019a , b ; Supplementary Figures 1 – 19 ). Since hev-peptides contain 38–42 amino acids and eight cysteine residues, we focused on peaks around 4 kDa in their MS profiles.…”
Section: Resultsmentioning
confidence: 99%
“…Cysteine-rich peptides cross-linked by multiple disulfides are known for their stability against heat, acid, and proteolytic degradation ( Kini et al, 2015 , 2017 ; Loo et al, 2016 , 2017 , 2021a , b ; Wong et al, 2016 ; Tam et al, 2018 ; Kam et al, 2019a , b ). To investigate the involvement of the disulfide scaffold on the stability of avenatides, we performed peptide degradation assays on folded avenatide aV1 and compared with its linearized S -alkylated form.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the type and extent of the injury, a prolonged influx of inflammatory cells, an imbalance in the myofibroblast turnover, and/or a disorganized extracellular matrix organization may occur, thereby resulting into corneal scarring and opacity (Bukowiecki et al, 2017). Previously, we showed that both EGF and bleogen pB1 are mitogens that can accelerate incisor eruption in newborn mice and skin wound healing in streptozotocin-induced diabetic rats (Loo et al, 2021a). Similar to EGF, bleogen pB1 activates the EGFR/MEK/ERK signaling pathway in keratinocytes to trigger cell proliferation in healing skin wounds.…”
Section: Figurementioning
confidence: 99%
“…Recently, our laboratory discovered and identified the first plant-derived EGFR agonist known as bleogen pB1 ( Loo et al, 2021a ). Bleogen pB1 is a 36-residue miniprotein and the smallest known EGFR agonist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation